2015
DOI: 10.1007/s40292-015-0117-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Fixed-Dose Perindopril/Amlodipine on Clinic, Ambulatory and Self-Monitored Blood Pressure and Blood Pressure Variability: An Open-Label, Non Comparative Study in the General Practice

Abstract: The three main methods of BP assessment showed that substituting ineffective antihypertensive therapy with FDC perindopril/amlodipine resulted in a rapid and pronounced antihypertensive effect, with target BP levels achieved after 3 months in most patients. This beneficial effect was observed also on various parameters related to BP variability, which may reflect additional cardioprotective properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Provision of an automatic BP monitor [31] and optimization of the drug regimen using fixed combinations [11, 15, 16, 18, 19, 32, 33, 35, 36] found to be effective elsewhere [45, 46], were associated with a significant increase in adherence to AHT. However, in several of the studies adherence also improved in control groups, most likely because both groups received a series of enhancements to treatment including self-monitoring diaries, and written recommendations on lifestyle changes, as well as intensive monitoring of both groups for the entire period of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Provision of an automatic BP monitor [31] and optimization of the drug regimen using fixed combinations [11, 15, 16, 18, 19, 32, 33, 35, 36] found to be effective elsewhere [45, 46], were associated with a significant increase in adherence to AHT. However, in several of the studies adherence also improved in control groups, most likely because both groups received a series of enhancements to treatment including self-monitoring diaries, and written recommendations on lifestyle changes, as well as intensive monitoring of both groups for the entire period of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, calcium channel blockers, thiazide diuretics can improve BPV at different levels. The effect of angiotensin converting enzyme inhibitors, angiotensin receptor blockers on BPV is inconsistent, and β-blockers could increase BPV [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The ABPM substudy of PEARL (PErindopril/Amlodipine Reduction of blood pressure Level), a 3-month observational study, demonstrated a statistically significant reduction in systolic and diastolic withinindividual visit-to-visit BP variability, as assessed by the systolic and diastolic BP coefficient of variation, from 10.5/13.5% at baseline to 8.2/11.7% (P < 0.01) after 3 months [73]. In addition, an open-label study in general practice which examined the effect on BP of substituting current ineffective antihypertensive treatment with a fixed-dose combination of perindopril/amlodipine in patients with uncontrolled hypertension showed that target BP levels were achieved in the majority of patients at 3 months, with additional beneficial effects on various parameters related to BP variability [74].…”
Section: Indexmentioning
confidence: 99%